The Effect of Product Design and Digital Marketing on Buying Interest of TXT Boygroup Album Among K-pop Fans Generation Milennials and Z - Aditya Pradipta, Naura; Zumrotul Fitriyah; Wilma Cordelia Izaak (PT Inovasi Pratama Internasional, 2024)
This study is aimed to determine the impact of the Product Design, Digital Marketing and Buying Interest on the album of the boygroup TXT among K-pop Fans. The population in this Research is K-pop fans generation millennials and z. The sample in this study used convenience sampling and found 117 respondents. The primary data collection method in this study uses a questionnaire in the form of a google form. The data analysis technique in this study uses PLS (Partial Least Square). The result of this study indicates that the variable of Design Product and Digital Marketing has a positive and significant influence on Interest Buying.